VALIDASI PERSAMAAN BATAS KERUSAKAN MANGGA ARUMANIS BERDASARKAN ZERO MOMENT POWER - Warji Warji; Suroso Suroso; Rokhani Hasbullah (Teknologi Hasil Pertanian Fakultas Pertanian Universitas Lampung, 2007)
The objectives of this research were to validate the border equation of arumanis mangoes damage caused by fruit fly using zero moment power (Mo) number. The method is based on measurement of zero moment power ultrasonic wave in arumanis mangoes. Results showed that mean of Mo number normal arumanis mangoes was 4,58 and Mo number arumanis mangoes damage caused by fruit fly was 6,40. Prediction equation was Mo number more than 5,60 for normal mango and Mo number less than or same 5,60 for mangoes invested by fruit fly. Keywords: ultrasonic, arumanis mangoes, fruit fly, Mo number, validation.